Exploring Mental Health Programs in Mental Health Literacy: A Literature Review - Nurdin, Andi Ardiansyah; Shaluhiyah, Zahroh; Widjanarko, Bagoes (Poltekita : Jurnal Ilmu Kesehatan, 2024)
Mental health is an essential part of human life and society. Poor mental health affects well-being, ability to work, and relationships with friends, family, and community. The prevalence of mental health problems is also increasing every year. Mental health literacy can be a key foundation in efforts to prevent chronic mental disorders. This study aimed to identify literature studies on mental health literacy interventions. Articles were searched on search engines (Ebsco, PubMed, Science Direct, and Scopus) by using the keywords mental health literacy, intervention, and adolescents. The inclusion criteria are quantitative research with experimental design on adolescent samples, the last 3 years period 2021-2023 while the exclusion criteria are qualitative, cross-sectional, and pilot studies, adult samples, and research in 2020 and below. 10 articles met the criteria. The results of the literature review show that mental health interventions can improve mental health literacy in adolescents. Recommendations from this literature review can be used as policy material for authorized stakeholders in efforts to promote and prevent mental health in adolescents.